Genetic coding variant in complement factor B (CFB) is associated with increased risk for perianal Crohn’s disease and leads to impaired CFB cleavage and phagocytosis - Stamps, Dalton T; Dube, Shishir; Li, Dalin; Yang, Shaohong; Landers, Carol J; Mengesha, Emebet; Murali, Ramachandran; Potdar, Alka A; Wolf, Andrea J; Botwin, Gregory J; Khrom, Michelle; Faubion, William A; et al. (Gut, 2023)
ObjectivePerianal Crohn’s disease (pCD) occurs in up to 40% of patients with CD and is associated with poor quality of life, limited treatment responses and poorly understood aetiology. We performed a genetic association study comparing CD subjects with and without perianal disease and subsequently performed functional follow-up studies for a pCD associated SNP in Complement Factor B (CFB).DesignImmunochip-based meta-analysis on 4056 pCD and 11 088 patients with CD from three independent cohorts was performed. Serological and clinical variables were analysed by regression analyses. Risk allele of rs4151651 was introduced into human CFB plasmid by site-directed mutagenesis. Binding of recombinant G252 or S252 CFB to C3b and its cleavage was determined in cell-free assays. Macrophage phagocytosis in presence of recombinant CFB or serum from CFB risk, or protective CD or healthy subjects was assessed by flow cytometry.ResultsPerianal complications were associated with colonic involvement, OmpC and ASCA serology, and serology quartile sum score. We identified a genetic association for pCD (rs4151651), a non-synonymous SNP (G252S) in CFB, in all three cohorts. Recombinant S252 CFB had reduced binding to C3b, its cleavage was impaired, and complement-driven phagocytosis and cytokine secretion were reduced compared with G252 CFB. Serine 252 generates a de novo glycosylation site in CFB. Serum from homozygous risk patients displayed significantly decreased macrophage phagocytosis compared with non-risk serum.ConclusionpCD-associated rs4151651 in CFB is a loss-of-function mutation that impairs its cleavage, activation of alternative complement pathway, and pathogen phagocytosis thus implicating the alternative complement pathway and CFB in pCD aetiology.